Caracterización zoométrica y faneróptica en gallinas criollas desde el nacimiento hasta el dimorfismo sexual en las parroquias El Tambo, Zambi y San Pedro de la Bendita del cantón Catamayo - Carrión Rojas, Pablo Rafael (2019)
In order to evaluate the morphometric and phaneroptic characteristics of the na- tive birds of the El Tambo, Zambi and San Pedro de la Bendita parishes of the Cata- mayo canton, Were used 230 birds, 63 females and 167 males, which were raised in the facilities of the Quinta Experimental Punzara from birth to sexual dimorphism. Were measured 14 quantitative variables and 10 qualitative variables, these measure- ments were registered every 15 days, the birds were weighed with a digital scale and measured with a measuring tape and a staircase. In relation to the zoomometric varia- bles, it was determined that the most significant measures in females and males were: weight, dorsal length, thoracic perimeter and leg length in the Zambi parish. All the measures showed a very strong positive correlation but the highest correlations were for the tarsal length (0,99) in males and females. It was possible to determine through the phenoptic characteristics that the specimens of the cuban biotype, at one month of age, demonstrated characteristics of each sex, being in the males more pronounced than in the females. In relation to the phenoptic variables, the predominant plumage colors were dark with 76,9 % having a skin, tarsus and yellow beak 74,8 %; 44,8 % and 33 % respectively; The eye color found was 69,6 % brown and the feather distri- bution was normal 98,3 %. The data obtained were subjected to a descriptive statistic and the analyzes were performed using the RStudio statistical package version 3.5.1.